Doctor of Physical and Mathematical Sciences, Professor M.I. Ramazanov is 70 years old - Jenaliyev, M.T. (Bulletin of the Karaganda University. Mathematics Series, 2019)
Doctor of Physical and Mathematical Sciences, Professor M.I. Ramazanov turned 70 years old. Murat Ibraevich Ramazanov is a highly qualified specialist in the field of loaded partial differential equations, integral equations and their applications to applied problems. He regularly gives scientific reports at international congresses, conferences, and symposiums dedicated to discussing modern problems in mathematics, which are held in the Republic of Kazakhstan and abroad.